Ommatoiulus malleatus n. sp., a new Tunisian millipede, with notes on the punicus species group of Ommatoiulus (Diplopoda, Julidae) - Akkari, Nesrine; Voigtländer, Karin (Zootaxa, 2007)
A new millipede species, Ommatoiulus malleatus n. sp. (Diplopoda, Julidae), is described from the Ichkeul National Park, Tunisia. The gonopod structure of the species indicates the punicus-group which includes Ommatoiulus punicus (Brölemann, 1894), Ommatoiulus seurati (Brolemann, 1925), Ommatoiulus aumalensis (Brolemann, 1925), Ommatoiulus atlanteus Schubart, 1960, Ommatoiulus quadridentatus Schubart, 1960 recorded from North Africa and Ommatoiulus brandti (Berlese, 1885) from Sicily. The new species is, however, well differentiated by a particular “hammer-like structure” on the mesomerite process of the posterior gonopod.